Bentuk Eksploitasi Anak yang Terjadi di Kota Gorontalo - Ismail Yusuf (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out what forms of child exploitation occur in the city of Gorontalo and how legal sanctions are applied to perpetrators of child exploitation from the perspective of criminal law and jinayah jurisprudence. This research is field research, namely field observations of the objects being studied in order to obtain relevant data about matters related to the problem being studied and which focuses on the results of data collection from predetermined informants. This field research is outlined in a design that provides a clear and accurate picture of the materials and phenomena being studied. The data obtained in this research is still expressed in qualitative form, which has a richer meaning than numbers and frequencies. The results of this research show that (In Human Rights instruments there are five forms of criminal acts of sexual exploitation of children, namely: child prostitution; child pornography; trafficking in children for sexual purposes; child sex tourism and child marriage. Currently there are the newest forms of crime from this act. criminal exploitation of children, namely the application of legal sanctions against perpetrators of child exploitation from the perspective of criminal law and fiqh jinayah, namely the application of legal sanctions against perpetrators of child exploitation from the perspective of criminal law and the application of legal sanctions against perpetrators of child exploitation from the perspective of fiqh Jinayah.